Personal sense of power, emotion and compliance in the workplace: a moderated mediation approach. Issue 1 (5th June 2020) - Laslo-Roth, Roni; Schmidt-Barad, Tomer
Abstract : Purpose: The purpose of this study was to investigate the associations between personal sense of power (PSP) and compliance as a function of the interaction between negative emotion intensity and emotion regulation tactics. Design/methodology/approach: First, hypotheses linking PSP to different emotional reactions and to different levels of compliance with two types of conflict management styles were formulated. Subsequently, data were collected in three waves with a five-week interval between them to test the hypotheses. Findings: Results based on principle component analysis and confirmatory factor analysis indicated that workers with high PSP reported lower internalized negative emotions (negative emotions directed to the self) in the workplace and were less inclined to comply with harsh tactics, in comparison to workers with low PSP. The importance of emotional components (suppression and negative emotions in the workplace) was underscored by the moderated mediation model: internalized negative emotions mediated the association between PSP and compliance with harsh tactics as a function of level of suppression such that the link between negative affect and compliance was negative only under high suppression, but not under low suppression. Research limitations/implications: The findings point to the deleterious influence of high emotional suppression of negative emotions on study behaviors, especially for employees with a low sense of power. Because the data were collected from a single source, which could raise concerns about common method variance and social desirability bias, future study should examine other-reports. Practical implications: Recruitment and training of employees and managers should aim to create an open and safe organizational environment that encourages emotional expression and lessens emotional suppression. Social implications: The findings can help develop empowering interventional programs to coach employees to use suppression in an adaptive manner. Originality/value: The current study sheds new light on the relationships between PSP and compliance from the emotion regulation perspective.